Testing of Various Solvents for the Preparation of Lipid Samples for Use in Thin Layer Chromatography - Odagiu, Antonia; Sălăjan, Gheorghe; Mierliţă, Daniel; Georgescu, Bogdan; Dinea, Mariana (Acta Agraria Debreceniensis, 2001)
We analyzed the muscular tissue of 6 sheep. Lipid extraction was performed using the Handson and Olley method. TLC separation was performed using 4 separation systems and the best separation method was determined. Visualization was done using a mixture copper acetate and phosphoric acid, at 150 oC.